Improving Temporal Trends in Survival and Neurological Outcomes After Out-of-Hospital Cardiac Arrest. Issue 1 (January 2018) - Buick, Jason E.; Drennan, Ian R.; Scales, Damon C.; Brooks, Steven C.; Byers, Adams; Cheskes, Sheldon; Dainty, Katie N.; Feldman, Michael; Verbeek, P. Richard; Zhan, Cathy; Kiss, Alex; Morrison, Laurie J.; et al.
Abstract : Background: Considerable effort has gone into improving outcomes from out-of-hospital cardiac arrest (OHCA). Studies suggest that survival is improving; however, prior studies had insufficient data to pursue the relationship between markers of guideline compliance and temporal trends. The objective of the study was to evaluate trends in OHCA survival over an 8-year period that included the implementation of the 2005 and 2010 international cardiopulmonary resuscitation (CPR) guidelines. Methods and Results: This was a population-based cohort study of all consecutive treated OHCA patients of presumed cardiac cause between 2006 and 2013 in the City of Toronto, Canada, and surrounding regions. Temporal changes were measured by χ 2 trend test. The association between year of the OHCA and survival was evaluated using logistic regression and joinpoint analysis. A total of 23 619 patients with OHCA met study inclusion criteria. During the study period, survival to hospital discharge doubled (4.8% in 2006 to 9.4% in 2013; P <0.0001), and survival with good neurological outcome increased (6.2% in 2010 to 8.5% in 2013; P =0.005). Improvements occurred in the rates of bystander CPR and automated external defibrillator application, high-quality CPR metrics, and in-hospital targeted temperature management. After adjusting for the Utstein variables, survival to hospital discharge (odds ratio, 1.12; 95% confidence interval, 1.09–1.15) and survival with good neurological outcome (odds ratio, 1.13; 95% confidence interval, 1.05–1.22) increased with each year of study. Conclusions: Survival after OHCA has improved over time. This trend was associated with improved rates of bystander CPR, automated external defibrillator use, high-quality CPR metrics, and in-hospital targeted temperature management. The results suggest that multiple factors, each improving over time, may have contributed to the observed increase in survival. Abstract : Supplemental Digital Content is available in the text.